Ethnic group and social support contribution to posttraumatic growth after sudden spousal loss among Jewish, Muslim, and Druze widows in Israel. Issue 5 (28th March 2021) - Khatib, Anwar; Ben‐David, Vered; Gelkopf, Marc; Levine, Stephen Z.
Abstract: This study aimed to examine the contribution of ethnic group status and social support to posttraumatic growth (PTG) among widows after sudden spousal loss. Participants included 184 widows from three ethnic groups: 59 (32.3%) Jewish, 58 (31.7%) Muslim, and 66 (36%) Druze. Information was gathered via a demographic questionnaire, PTG Inventory, and Multidimensional Scale of Perceived Social Support. Analysis of covariance was used to test ethnic group status differences in social support, controlling for demographic variables. Hierarchical linear models were used to assess groups differences in the study outcome variables. The results showed that the PTG total score was higher for Jewish widows than for Muslim and Druze widows, with a null difference between the latter two, and social support contributed to increased PTG among Jewish widows more than among Muslim and Druze widows, with no significant association between social support and PTG among Druze widows. The highest PTG levels were observed among widows from modern individualistic cultural backgrounds, compared with traditional collectivist, cultural backgrounds after sudden spousal death. The social support system may be a pathway to enhance PTG among widows in traditional collectivist societies.